Flavonoid contents and 2,2-diphenyl-1 -picrylhydrazyl radical scavenging activity of some edible mushrooms from Turkey: A bisporus and pleurotus Spp - Akyüz, Mehmet; Onganer, Ayse Nilay; Erecevit, Pinar; Kirbag, Sevda (My University, 2012)
In this study; flavonoid and resveratrol contents and 2,2-diphenyl-l- picrylhydrazyl (DPPH) free radical scavenging activities of Agaricus bisporus, Pleurotus eryngii var. eryngii, P. eryngii var. ferulae, P. sajor-caju, P. ostreatus and Pleurotus sp. florida were determined In addition, the amounts of resveratrol and flavonoid such as rutin, myricetin, morin, quercetin, kaempferol cate chin, naringenin were also determined to be 0.00-0:75 and 0.00-3.00, 0.00-11.75, 0.00- 64.50, 0.00-0.50, 0.00-0.25, 0.00-396.00, 0.00-2.00 ?g/g of dry weight, respectively. Furthermore, naringin was not detected in any of the samples. EC50 value in scavenging ability on DPPH free radical was 11.78% in P. ostreatus, 13.01% in P. sajor-caju, 13.11% in P. eryngii var. eryngii, 14.58% in Pleurotus sp. florida, 17.25% in A. bisporus and 24.67% in P. eryngii var. ferulae. In fact, P. ostreatus was the most efficient species concerning antioxidant activity, while P. eryngii var. ferulae presented lower antioxidant properties. Based on EC$0 values, P. ostreatus was good in antioxidant properties for the scavenging ability on DPPH free radical. Copyright © 2012 by New Century Health Publishers, LLC.
Keywords: A. bisporus; Antioxidant activity; Edible mushroom; Flavonoid content; Pleurotus spp